Health System Reform in the United States - John E McDonough (Kerman University of Medical Sciences, 2014)
In 2010, the United States adopted its first-ever comprehensive set of health system reforms in the Affordable Care Act (ACA). Implementation of the law, though politically contentious and controversial, has now reached a stage where reversal of most elements of the law is no longer feasible. The controversial portions of the law that expand affordable health insurance coverage to most U.S. citizens and legal residents do not offer any important lessons for the global community. The portions of the law seeking to improve the quality, effectiveness, and efficiency of medical care as delivered in the U.S., hold lessons for the global community as all nations struggle to gain greater value from the societal resources they invest in medical care for their peoples. Health reform is an ongoing process of planning, legislating, implementing, and evaluating system changes. The U.S. set of delivery system reforms has much for reformers around the globe to assess and consider.